COMPARISON OF EFFICACY OF ANGIOTENSIN CONVERTING ENZYME INHIBITOR (ACEIS) V/S ANGIOTENSIN II RECEPTOR BLOCKERS (ARBS) IN MANAGEMENT OF MICRO ALBUMINURIA AMONG NORMOTENSIVE TYPE 2 DIABETIC PATIENTS: Ace-is V/S ARBS for Micro Albuminuria in Type 2 Diabetics - Tahir, Muhammad; Hassan, Wahaj Ul; Alam, Haji Muhamamd Aftab (Pakistan Armed Forces Medical Journal, 2016)
Objective: To compare the efficacy of Angiotension Converting Enzyme (ACEIs) v/s Angiotensin II Receptor Blockers (ARBs) in management of micro albuminuria among normotensive type 2 diabetic patients.Study Design: Randomized controlled trial.Place and Duration of Study: Department of Medicine, Combined Military Hospital, Kohat from Oct 2011 to Mar 2012.Material and Methods: A total of 356 patients (178 in each group) between 30 and 60 years of age with newly diagnosed diabetes and having microalbuminuria fulfilling the inclusion criteria were selected through consecutive sampling and were enrolled in study. Patients were divided into two groups by random sampling. Group-1 (ACEIs) received enalapril 10mg/day while group-2 (ARBs) received losartan 50mg/day. Confounding variables were excluded using exclusion criteria.Results: Mean age of the patients was 53.8 ± 8.7 and 53.1 ± 9.5 years in group-1 and group-2, respectively. Majority of patients in both groups were male. Efficacy was observed in 154 patients (86.5%) of group-1 and in 157 patients (88.2%) of group-2. Difference between two groups was non-significant (p>0.05).Conclusion: ACEIs and ARBs both protect type 2 diabetic patients from developing protienuria.